Efficient nitric oxide electroreduction toward ambient ammonia synthesis catalyzed by a CoP nanoarray. Issue 7 (18th February 2022) - Liang, Jie; Hu, Wen-Feng; Song, Bingyi; Mou, Ting; Zhang, Longcheng; Luo, Yongsong; Liu, Qian; Alshehri, Abdulmohsen Ali; Hamdy, Mohamed S.; Yang, Li-Ming; Sun, Xuping
Abstract : A CoP nanoneedle array supported on Ti mesh acts as a high-active electrocatalyst with a low onset potential toward NO-to-NH3 conversion, achieving a faradaic efficiency of 88.3% and a yield of 47.22 μmol h −1 cm −2 . Abstract : The ever-increasing anthropic NO emission from fossil fuel combustion has resulted in a series of severe environmental issues. Ambient electrocatalytic NO reduction has emerged as a promising route for sustainable NO abatement and energy-saving NH3 synthesis, but it is kinetically complex and energetically challenging, thus requiring electrocatalysts with high activity and selectivity. Herein, we demonstrate the direct use of a CoP nanowire array on Ti mesh (CoP/TM) as an efficient hydroprocessing catalyst for electrochemically converting NO to NH3 . This monolithic catalyst achieves a faradaic efficiency of 88.3% and an NH3 yield of 47.22 μmol h −1 cm −2, much superior to its Co(OH)F counterpart (30.3%, 4.21 μmol h −1 cm −2 ). Significantly, it exhibits high durability and negligible activity decay for 14 h bulk electrolysis. The excellent electrocatalytic NO reduction activity of our CoP/TM is demonstrated further by using it as a Zn–NO battery cathode catalyst. Theoretical calculations reveal the catalytic mechanisms.